2020
DOI: 10.46572/nat.2020.11
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of Students About Distance Education in the Pandemi Process

Abstract: While the pandemic process experienced all over the world has caused digital transformations in many areas, it has also caused some obligations in the field of education. Distance education has become an imperative this process in Turkey. Private or public institutions that provide education and training at all levels continued their activities through distance education. This study was carried out to determine student views on distance education. The working group consists of 508 students studying in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…In addition, it was observed that most of them were indecisive in determining whether online education had a positive or negative impact at a cognitive level. However, men were more positive toward online education than women [18].…”
Section: Emergency Remote Teachingmentioning
confidence: 82%
“…In addition, it was observed that most of them were indecisive in determining whether online education had a positive or negative impact at a cognitive level. However, men were more positive toward online education than women [18].…”
Section: Emergency Remote Teachingmentioning
confidence: 82%
“…As for the internal learning process itself, it is formed on such characteristic as the pedagogic. It should be agreed that distance education differs in essence and in the way it is organized, so it gives applicants more motivation, in particular through interactivity and flexibility (Aksoğan, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…To prevent the pandemic, on March 18, 2020, Higher Education Institution (YOK) decided to stop face-to-face education activities at the associate, undergraduate, and postgraduate levels throughout the country in the spring term of the 2019-2020 academic year and the educational activities continued in the form of distance education (YOK, 2020). In the studies carried out with teacher candidates during the COVID-19 pandemic period in the literature, some negative results have been reported, such as the fact that distance education has a negative effect on the socialization of students (Aksogan, 2020), distance education is not suitable for every course (Shim & Lee, 2020), it is difficult to communicate in distance education (Karatepe et al, 2020); students have a negative attitude towards distance education (Yolcu, 2020), they have motivational problems (Hebebci et al, 2020) and technical difficulties (Karakus et al, 2020). However, it is possible to reach positive results such as the fact that the lessons are independent of time and place (Ardic, 2021), students have the opportunity to listen to the lessons again (Sakarya & Zahal, 2020), and that they are economical (Piskin Tunc & Akinci, 2020).…”
Section: Introductionmentioning
confidence: 99%